Optimizing E-commerce Sales of Handwritten Batik to MSMEs Handwritten Batik Lasem Sranti - Farikhah, Izzah; Khoiron, Agus Ahmad; Hanantyo, Burhanuddin (Labkat Press KA FTIK UNIKOM, 2024)
This study aims to improve the competitiveness and implementation of e-commerce in Lasem Batik Tulis MSMEs in the digital era. Through the use of information technology and online platforms such as Shopee and Tokopedia, this study helps MSMEs improve their sales competitiveness. Research methods include observation, interviews, analysis of existing conditions, proposals for e-commerce platforms, account creation, mentoring, and evaluation. The results show that the integration of digital technology provides significant benefits by expanding market reach and accelerating the marketing process. Training in the use of digital platforms also improves the skills of Lasem batik artisans. This mentoring provides a holistic perspective on increasing the competitiveness of MSMEs amid digital transformation. These results are expected to increase the income and sustainability of the Indonesian traditional batik industry. Adaptation of digital technology not only expands market access but also increases operational efficiency and digital marketing capabilities of MSME actors. This success emphasizes the importance of adopting technology to support the sustainability and competitiveness of the Indonesian creative industry. The results of the mentoring confirm that digitalization is a strategic step to face the challenges of the global market in the digital era, especially for MSMEs in the batik tulis industry.